Practicality of e-student worksheets on moss plant (bryophyta) material to improve critical thinking ability in MAN 3 Banjarmasin - Nurul Fajriyah; Khairunnisa Khairunnisa; Ita Ita (HAFECS PRESS, 2024)
The Electronic Student Worksheet (E-LKPD) on the topic of moss plants is a teaching material developed into an electronic medium to enhance students' critical thinking skills. However, it has not yet undergone practicality testing. This study aims to describe the practicality results of developing the student worksheet on the topic of moss plants (Bryophyte) as teaching material to improve students' critical thinking skills at MAN 3 Banjarmasin. This research employs the Education Design Research (EDR) method with Tessmer's formative evaluation, limited to individual tests (one-to-one) and small group evaluations. The research data were collected using a content practicality questionnaire and an expected practicality questionnaire. The results show that the content practicality achieved an overall average score of 95.83% (very good/feasible), while the expected practicality achieved an overall average score of 97.22% (very good). Based on these findings, it can be concluded that all aspects of practicality scored within the